TV news and "white voices" - Vaagan, Robert W. (Javnost (Ljubljana), 2010)
The media blockade imposed by Israel during its 22-day invasion of Gaza in December 2008 - January 2009 barred foreign reporters from entering Gaza. Eye witness reports were restricted to the invading Israeli military and to Palestinian and Arab journalists in Gaza. The blockade influenced media coverage and public opinion around the world. Two Norwegian aid workers and medical doctors managed to enter Gaza on the fifth day of the war to work at the Hamas-controlled Al Shifa Hospital. As the only Western doctors, they were interviewed repeatedly by global media. They frequently appeared also in Norwegian media, including Dagsrevyen, the prime time evening TV news of NRK -The Norwegian State Broadcasting Corporation. They attributed their media appearances to their "white voices," i.e. local Palestinian and Arab voices were less interesting to Western media. Drawing on framing theory, content analysis and interviews, we first discuss possible bias and framing in Dagsrevyen's coverage of the Gaza War as it ran its course. We also reflect onpost-war developments, before addressing the two Norwegian doctors and their media relations during and after the war. Were their interactions with the media "source-driven journalism," and how justified is their "white voices" claim?
Keywords: mass media; množični mediji; informiranje; obveščanje; svoboda tiska; vojna; war; Gaza; Israel; Izrael; Norveška